2011
DOI: 10.1002/jmv.22131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical effects of betamethasone in human t‐cell lymphotropic virus type‐i‐associated myelopathy/tropical spastic paraparesis patients

Abstract: There is no effective therapy for human T-cell lymphotropic virus type I (HTLV-I)-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Glucocorticoids are effective to reduce the motor disability in these patients, but its role as anti-spastic drugs is unknown. Here it is reported the use of corticosteroids in HAM/TSP. The goal was to find reliable molecular markers linked to treatment effectiveness. The clinical efficacy of corticosteroids was studied in 22 HAM/TSP. The treatment was a single dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Moreover, corticosteroids may also affect the HTLV-I infected cells or the immune response to HTLV-I. It has been demonstrated that betamethasone therapy decreased CD4 (24). Corticosteroids therapy may reduce the erratic IFN-γ production by T-cells in patients with HAM/TSP, which is then followed by a reduction of neopterin release by the stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, corticosteroids may also affect the HTLV-I infected cells or the immune response to HTLV-I. It has been demonstrated that betamethasone therapy decreased CD4 (24). Corticosteroids therapy may reduce the erratic IFN-γ production by T-cells in patients with HAM/TSP, which is then followed by a reduction of neopterin release by the stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…+ cytotoxic T lymphocytes, 20 nM concanamycin A was added to the culture media (Sigma-Aldrich, St Louis, MO) as performed by Alberti et al (2000). 42 The counting of viable and nonviable cells was measured by 0.4% trypan blue exclusion dye (Sigma-Aldrich). This method showed more than 95% viable PBMCs, which agrees with the manufacturer's statement (Amersham Bioesciences).…”
Section: Methodsmentioning
confidence: 99%
“…42 Cells were harvested and stained with fluorophore-conjugated antibodies from eBiosciences (San Diego, CA): CD4-PE (Catalog No. PBMCs cultured in RPMI 1640 + GlutaMAX, 10% iFBS, and 20 nM concanamycin A were treated with or without anti-Tax (Covalab, Catalog No.…”
Section: Pbmcs Flow Cytometrymentioning
confidence: 99%
“…After 24 h culture, PBMCs from HTLV-1-infected patients expressed Tax protein at detectable levels by flow cytometry, 7 but not by western blot. Nevertheless, secreted Tax can be followed by western blot in PBMC culture medium, which indicates Tax secretion.…”
Section: Tax Expression In Cultured Pbmcs From Infected Subjectsmentioning
confidence: 99%
“…3,4 Regarding infection, T-CD4 + cells are the in vivo reservoir of the virus, mainly CD4 + FoxP3 + cells or T reg . [5][6][7] Human cerebral endothelial cells have been shown to be susceptible to retroviral infection, producing a dysfunction of the blood-brain barrier by alteration in the expression of tight-junction proteins. 8 This could be an important mechanism for the infiltration of infected lymphocytes into the central nervous system (CNS) and also facilitates astrocyte infection.…”
mentioning
confidence: 99%